PENGARUH AKTIVASI ASAM DAN PROSES HIDROTERMAL TERHADAP PENINGKATAN HIDROFOBISITAS LEMPUNG ALAM - , PRIYAGUNG DHEMI W ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In this research, the enhancement in hydrophobicity of natural clay has been done with two sequential techniques that were acid activation technique and hydrothermal technique. Acid activation was done by refluxing natural clay with HCl solution at 90oC for 6 hours. The concentrations of HCl used were varied at 2, 4, and 6 M. Hydrothermal technique was done by heating the mixture containing acid-activated clay, NaOH solution, ethanol, and TPA Br in an autoclave at 170oC for 24 hours with the variations of aging time at 24, 72, and 168 h. After hydrothermal process, the materials were calcined at 600oC to remove the organic template. Materials obtained in every technique were analyzed for the mass change and the water adsorption then characterized with infrared spectrometer to identify the functional group and X-ray difractometer to identify the crystallinity of minerals. Acid activation technique was able to enhance the hydrophobicity of natural clay and the highest result is obtained from the activation with HCl 6M. The water adsorption decreased from 0,13 to 0,06 g/g materials. Hydrothermal treatment also enhanced hydrophobicity of the clay with the highest result was obtanined by aging for 24 hours. The water adsorption was decreased from 0,076 to 0,03 g/g material.